Dietary-Induced Elevations of Triglyceride-Rich Lipoproteins Promote Atherosclerosis in the Low-Density Lipoprotein Receptor Knockout Syrian Golden Hamster - Lin, Xiao; Ma, Ping; Yang, Chun; Wang, Jinjie; He, Kunxiang; Chen, Gonglie; Huang, Wei; Fan, Jianglin; Xian, Xunde; Wang, Yuhui; Liu, George (Frontiers in Cardiovascular Medicine, 2021)
Elevated triglycerides are associated with an increased risk of cardiovascular disease (CVD). Therefore, it is very important to understand the metabolism of triglyceride-rich lipoproteins (TRLs) and their atherogenic role in animal models. Using low-density lipoprotein receptor knock out (LDLR-/-) syrian golden hamsters, this study showed that unlike LDLR-/- mice, when LDLR-/- hamsters were fed a high cholesterol high fat diet (HFD), they had very high plasma levels of triglycerides and cholesterol. We found that LDLR-/- hamsters exhibited increased serum TRLs and the ApoB100 and 48 in these particles after fed with HFD. Treatment with ezetimibe for 2 weeks decreased these large particles but not LDL. In addition, ezetimibe simultaneously reduced ApoB48 and ApoE in plasma and TRLs. The expression of LRP1 did not change in the liver. These findings suggested that the significantly reduced large particles are mainly chylomicron remnants, and further, the remnants are mainly cleared by the LDL receptor in hamsters. After 40 days on a HFD, LDLR-/- hamsters had accelerated aortic atherosclerosis, accompanied by severe fatty liver, and ezetimibe treatment reduced the consequences of hyperlipidemia. Compared with the serum from LDLR-/- hamsters, that from ezetimibe-treated LDLR-/- hamsters decreased the expression of vascular adhesion factors in vascular endothelial cells and lipid uptake by macrophages. Our results suggest that in the LDLR-/- hamster model, intestinally-derived lipoprotein remnants are highly atherogenic and the inflammatory response of the endothelium and foam cells from macrophages triggered atherosclerosis. The LDL receptor may be very important for chylomicrons remnant clearance in the Syrian golden hamster, and this may not be compensated by another pathway. We believe that the LDLR-/- hamster is a good model for the study of TRLs-related diseases as it mimics more complex hyperlipidemia.